ESTUDIO DEL EFECTO DEL ACEITE DE ORÉGANO (Origanum vulgare) Y BACTERIOCINA A PARTIR DE Weissella confusa EN LA CONSERVACIÓN DE DOS ESPECIES DE PESCADO: PAICHE (Arapaimas gigas) Y ALBACORA (Thunnus alalunga) MEDIANTE TÉCNICAS DE ENCAPSULAMIENTO - Quiroz Ramón, Ruth Elizabeth (2023)
The purpose of this research is to study the beneficial effects of the application of Origanum vulgare (Oregano) oil and the Weissella confusing bacteriocin on two types of fish different from the one we commonly find, such as paiche and albacore, because these have properties To preserve the chemical, bromatological and organoleptic characteristics, three types of methods were also used, wet salting, salting and vacuum fresh, for which bromatological analyzes were carried out on each of the treatments and then the best microbiological treatment was determined.